Kontinuum dalam WEB NHK NEWS pada Bulan Mei 2024 - Telsanggi, Hazaqwa; Ainiyah, Qurrotul; Muna, Aufa; Eliazar, Yuanito; Wiyatasari, Reny (Universitas Airlangga, 2024)
Linguistics is a discipline that delves into various aspects of language, including the formation, usage, and articulation of language by its speakers. Linguistics helps us to understand the mechanisms behind language formation, the reasons for its use, and how language is articulated within society. This study analyzes continuum words that appear in news articles on the NHK NEWS website in May 2024, with the aim of exploring the processes of word formation and conducting a morphophonemic analysis of these words. Using a qualitative approach, eight continuum words were analyzed to uncover the formation of morphemes and their meanings. The results indicate that these continuum words combine kango and gairaigo, without wago, effectively condensing complex concepts into concise terms for media communication. The morphophonemic analysis reveals sound changes and zero morphophonemics, reflecting the efficiency of the Japanese language in summarizing complex concepts. Further research is recommended to explore the flexibility of the Japanese language in other contexts.